2017
DOI: 10.1093/mnras/stx1124
|View full text |Cite
|
Sign up to set email alerts
|

Extended red emission in IC59 and IC63

Abstract: We analysed new wide-field, wide-and narrow-band optical images of IC 59 and IC 63, two nebulae which are externally illuminated by the early B-star γ Cas, with the objective of mapping the extended red emission (ERE), a dust-related photoluminescence process that is still poorly understood, in these two clouds. The spatial distribution of the ERE relative to the direction of the incident radiation and relative to other emission processes, whose carriers and excitation requirements are known, provides importan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 69 publications
6
29
0
Order By: Relevance
“…Fortunately, the reflection nebula IC 63 gives us an opportunity to observe the two phenomena simultaneously in the same line of sight. The existence of ERE in IC 63 was first reported by Witt & Boroson (1990) and recently verified by Lai et al (2017). As shown in Fig.…”
Section: Ic 63 and Star #46supporting
confidence: 54%
See 1 more Smart Citation
“…Fortunately, the reflection nebula IC 63 gives us an opportunity to observe the two phenomena simultaneously in the same line of sight. The existence of ERE in IC 63 was first reported by Witt & Boroson (1990) and recently verified by Lai et al (2017). As shown in Fig.…”
Section: Ic 63 and Star #46supporting
confidence: 54%
“…Star #46, denoted by the arrow, appears right behind the strongest ERE emission in the PDR, produced by radiation from the early B-star γ Cas, incoming from the SW direction. The peak intensities of ERE are found immediately behind the hydrogen ionization fronts in regions also occupied by UV-pumped rotationally excited molecular hydrogen (for detail, see Lai et al (2017)).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the ERE in nebulae can be comparable in intensity to that of the scattered light underlying the ERE band (e.g. Lai et al 2017) as is the case in the diffuse ISM, the exciting spectrum in typical nebulae rises steeply in intensity from the optical to the far-UV by about two orders of magnitude, while the exciting ISRF spectrum in the diffuse ISM is comparatively flat in the UV-optical wavelength range. The reason that ERE is found to be brighter in nebulae than in the diffuse ISM is simply due to the much higher radiation density of the exciting photons, not as a result of a high quantum yield.…”
Section: Photon Conversion Efficiencymentioning
confidence: 98%
“…Also, the models are generally not mutually exclusive, although each model purports to provide the full explanation. It is not the aim of this review to discuss individual models in detail; such discussions can be found in the review by Witt and Vijh (2004) and in Lai et al (2017), but we will provide some guidelines for possible progress.…”
Section: Implications For Ere Modelsmentioning
confidence: 99%
See 1 more Smart Citation